Therapy, Pain & Training - Berrsche G; Schmitt H (Deutsche Zeitschrift für Sportmedizin)
Problem: Children and adolescents are exposed to high peak loads at an early age in junior competitive sports. Little is known in this age group about the injury-free occurrence of pain and the sport-related consumption of painkillers.Methodology: Narrative review with multivariate and paired keyword search for studies that evaluated localization-dependent, injury-free prevalence of pain, analgesic use, and determinants of use in junior competitive sports.Results: Derived from the few existing studies, a pronounced willingness to participate in competitions and training despite pain (playing hurt) is found in junior competitive sports among injury-free junior athletes. Analogous to adult competitive sports, analgesics, especially from the group of non-steroidal anti-inflammatory drugs, are used at an early stage. Especially in adolescents with increasing performance progress, in particular female athletes, the use of analgesics for joint pain has been documented. The consumption takes place for the compensation of post-exposure pain conditions but also prophylactically. The use of analgesics and the decision to take them are influenced by the immediate care environment in 2/3 of cases. A physician is involved in only 1 of 3 analgesic use decisions. Discussion: For exertional pain, a displacement mentality exists among many stakeholders in the junior setting. There is early, with age increasingly uncritical and excessive analgesic use. This consumption behavior harbors a high potential for abuse due to self-defined indications, procurement, dosage and duration of use. There is an individual need for a stronger appreciation of pain conditions by the caregivers in junior competitive sports with early consultation with a doctor, combined with the question of how much pain is allowed. Key Words: Pain Prevalences, Analgesics, Children And Adolescents, Sports